Advances on identification and animated simulations of radioactivity risk levels after Fukushima Nuclear Power Plant accident (with a data bank): A Critical Review - Kulahci, Fatih; Bilici, Ahmet (Springer, 2019)
This review study has been based on two main foundations as advances on the attainment of the risk radioactive fallouts levels, and the applications of methods for risk assessment to actual data and visual results, which are based on a 3-year study. A risk analysis model is developed with the animated simulations including the isotope distribution based on soil activity data, I-131 measured at 19 stations after the Fukushima accident. Probability distribution functions of the risk levels are obtained in addition to the probability of occurrence (risk) and the probability of non-occurrence (reliability) of the activity risks concerning I-131. The results are used for prediction of 60-day radioactive fallout subsequence and animated (.mp4) through simulations. [GRAPHICS] .
Keywords: Spatial modelling prediction; Kriging; Radionuclide migration; Long-range transport; Radioactive fallout; Risk assessment